1982
DOI: 10.3109/00016358209019814
|View full text |Cite
|
Sign up to set email alerts
|

A novel miniature bite force recorder and its clinical application

Abstract: Solid state components were used to construct a miniature bite force recorder suitable for registrations in large study groups. A semiconductor was chosen as the sensory unit. The complete recording system included a power supply, the bite force recorder, a chart recorder and a millivoltmeter. Laboratory calibration tests were performed to screen the limitations of the recorder. Series of loads were applied in the range from 10 to 1000 N. Eight females and eight males, 20 to 25 years old, were asked to produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
1

Year Published

1986
1986
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(60 citation statements)
references
References 6 publications
5
54
1
Order By: Relevance
“…Studies have demonstrated that the maximum bite force was 500 N 56) and recommended that any restoration in the molar area should be able to sustain an occlusal load of about 500 N 57) Therefore, when evaluating crowns in-vitro, it is thought that posterior metal-free restorations should withstand an occlusal force of at least 1,000 N, with the assumption that the mastication forces in the moist oral environment may weaken the restoration by up to half its known fracture resistance force 58,59) . FEA has been used to imitate the occlusal fracture resistance test done in this study to show stress points after applying load on those structures.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that the maximum bite force was 500 N 56) and recommended that any restoration in the molar area should be able to sustain an occlusal load of about 500 N 57) Therefore, when evaluating crowns in-vitro, it is thought that posterior metal-free restorations should withstand an occlusal force of at least 1,000 N, with the assumption that the mastication forces in the moist oral environment may weaken the restoration by up to half its known fracture resistance force 58,59) . FEA has been used to imitate the occlusal fracture resistance test done in this study to show stress points after applying load on those structures.…”
Section: Discussionmentioning
confidence: 99%
“…The unilateral bite force (N) was recorded by means of a strain gauge transducer (miniature bite force recorder; Kleven, Oslo, Norway) [9] placed on the lower first molar. According to our standard procedure [4], the transducer was covered with polyvinyl chloride tubes for protection, and the force was measured during maximum clenches (2 s duration) as the stored peak values on the digital display (AME, Mikro-Elektronikk, Horten, Norway).…”
Section: Anthropometrics and Bite Forcementioning
confidence: 99%
“…A miniature bite force recorder of the type described by Floystrand et al (1982) was used for measurement of bite force at the start of treatment and at the control visits during the treatment. For the measurements, thin acrylic splints covering the occlusal surfaces of the teeth in the two dental arches were made.…”
Section: Bite Force Measurementmentioning
confidence: 99%